Impact of Policy Shift on Elasticity of Substitution in Indian Non-Metallic Mineral Industry - Ganesan, S.; Rajanbabu, R. (Indian Journal of Marketing, 2009)
India, with diverse and significant mineral resources, is the leading producer of some of the minerals. Of the 89 minerals produced in India, 52 are non-metalic, 11 metallic, 4 fuel minerals and 22 minor minerals. The share of the mineral sector in the gross domestic product (GDP) of the country is around 3.5 percent while accounting for 10 percent share in the index of industrial production. Though 80 percent of the mines are in the private sector, yet 91 percent of the production in terms of size comes from the government owned mining ventures. Mining employs over 8 lakh persons. India is the largest producer of mica blocks and mica splitting; ranks third in the production of barites and chromites; 4th in iron ore, 6th in bauxite and manganese ore, and 10th in aluminum and 11th in crude steel. Iron- ore, copper-ore, chromites, zinc concentrates, gold, manganese ore, bauxite, lead concentrates and silver account for the entire metalic production. Limestone, magnesite, dolomite, barites, kaolin, gypsum, apatite and phosphorite, stealite and fluorite account for 92 percent of non-metallic minerals.